2005
DOI: 10.1053/j.gastro.2005.09.025
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of OCTN1/2 Variants Within the IBD5 Locus to Disease Susceptibility and Severity in Crohn’s Disease

Abstract: Background & Aims:Recent data suggest that polymorphisms in the organic cation transporter (OCTN) genes OCTN1 (SLC22A4) and OCTN2 (SLC22A5) represent disease-causing mutations within the IBD5 locus (chromosome 5q31). We investigated associations with disease susceptibility, phenotype, and evidence for epistasis with CARD15 in 679 patients with Crohn's disease (CD) or ulcerative colitis (UC). Methods: A total of 374 patients with CD, 305 patients with UC, and 294 healthy controls (HCs) were studied. Genotyping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
88
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 47 publications
11
88
1
Order By: Relevance
“…Also, in individuals who were negative for the IBD5 risk haplotype, we did not find a significantly increased frequency of the L503F-G-207C TC haplotype in CD cases versus controls. Our findings are consistent with several very recent studies of the contribution of these variants to CD susceptibility, [13][14][15] that do not support a causal role for these variants and are not consistent with the findings of Peltekova et al 12,25 Taken together, the weight of current evidence suggests that despite the effect of the L503F and G-207C variants on the function of the cation transporters OCTN1 and OCTN2, 12 they are unlikely to have a direct causal role in the pathogenesis of CD.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, in individuals who were negative for the IBD5 risk haplotype, we did not find a significantly increased frequency of the L503F-G-207C TC haplotype in CD cases versus controls. Our findings are consistent with several very recent studies of the contribution of these variants to CD susceptibility, [13][14][15] that do not support a causal role for these variants and are not consistent with the findings of Peltekova et al 12,25 Taken together, the weight of current evidence suggests that despite the effect of the L503F and G-207C variants on the function of the cation transporters OCTN1 and OCTN2, 12 they are unlikely to have a direct causal role in the pathogenesis of CD.…”
Section: Discussionsupporting
confidence: 93%
“…[13][14][15][16] The original purpose of our study was to fine-map the region of association with CD and to try to identify functional sequence variants that were directly related to pathogenesis. Our analysis of LD across the region is consistent with the model proposed by Daly et al 11 of discrete blocks characterized by stretches of high LD interspersed with short intervals of LD breakdown and high levels of recombination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies included diverse populations and originated from Canada [6,13,14], the UK [15][16][17][18], Germany [19], New Zealand [20], Spain [21], Italy [22,23], Belgium [24], Greece [25], Sweden [26] and Japan [27,28]. One Japanese and another Hungarian study with a small number of subjects found no association between OCTN 1&2 transporter polymorphisms and CD [28,29]; thus there could be ethnic differences in IBD5 locus mutations and propensity for Crohn's disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…I nflammatory bowel diseases (IBD), 4 Crohn's disease (CD) and ulcerative colitis, are disorders of unknown etiology characterized by chronic relapsing-remitting inflammation of the gastrointestinal tract. Pathophysiological and genetic evidence points to an important role of intestinal barrier function in the initiation and perpetuation of the disease (1-7).…”
mentioning
confidence: 99%